AB0018 TRANSCRIPTOMIC CHARACTERIZATION OF SINGLE PATHOGENIC MEMORY B CELLS IN RHEUMATOID ARTHRITIS. (June 2019) - Simaite, Deimante; Slot, Linda; Yaligara, Veeranagouda; Savova, Virginia; Reimertz, Claus; Struebing, Carsten; Dietrich, Axel; Rinaldis, Emanuele de; Didier, Michel; Herrmann, Matthias; Nestle, Frank; Scherer, Hans Ulrich; et al.
Abstract : Background: Autoantigen-specific B lymphocytes are crucial players in the development of rheumatoid arthritis (RA). Despite the fact that ACPA+ autoreactive memory B cells have been observed in the majority of RA patients for a long time, their properties still remain enigmatic. Objectives: In this study, we aimed to reveal transcriptomic nature of single pathogenic memory B cells from RA patients. Methods: Single-cell full-length RNAseq data was generated from ACPA+ and control memory B cells from 7 human donors with established rheumatoid arthritis and subjected to transcriptome analyses as well as B cell receptor (BCR) assembly. Results: Both transcriptome and BCR data was successfully generated from the majority of the sequenced cells. The success rate depended on chosen sequencing parameters as well as on a BCR assembling algorithm that was used. We observed expression of genes defining memory B cell population in our data as well as pathways crucial for their function. Conclusion: Taken together, gene expression and BCR sequence data obtained from the same single cell can give novel insights into the biology and role of B cells in the development of the disease. Acknowledgement: This work has received support from the EU/EFPIA Innovative Medicines Initiative 2 Joint Undertaking RTCure grant n° 777357. Disclosure of Interests: Deimante Simaite Employee of: Sanofi, Linda Slot Grant/research support from: Sanofi, Veeranagouda Yaligara Employee of: Sanofi, Virginia Savova Employee of: Sanofi, Claus Reimertz Employee of: Sanofi, Carsten Struebing Employee of: Sanofi, Axel Dietrich Employee of: Sanofi, Emanuele de Rinaldis Employee of: Sanofi, Michel Didier Employee of: Sanofi, Matthias Herrmann Employee of: Sanofi, Frank Nestle Employee of: Sanofi, Hans Ulrich Scherer Grant/research support from: Sanofi, BMS, Rene Toes Grant/research support from: Sanofi